(untitled) (Research, Society and Development, 2021)
The loss of teeth often leads to the extrusion of antagonistic teeth, which results in occlusal interference and inadequate space to restore the prosthetic space. A prerequisite during the orthodontic treatment of dental and skeletal malocclusions is made using orthodontic anchorages, defined simply as a resistance to unwanted tooth movement and is fundamentally the basis for treating various occlusal disorders. Anchorage is achieved by means of extra and intraoral devices and the teeth themselves, these methods being limited, requiring some resources such as temporary anchoring devices (DAT), mini-implants or mini- screws. Because they have a small diameter, mini-implants have easier insertion, which expands the range of possibilities of the installation site, being efficient in the treatment with intrusion, as they offer more options for the correction of malocclusions without depending so much on the patients. Therefore, mini- implants provide fewer side effects, more comfort, a simple technique to be performed and a low cost and effectiveness of orthodontic treatments, which increases their therapeutic predictability and reduces the need for the patient to collaborate.